2009
DOI: 10.1007/s11433-009-0191-1
|View full text |Cite
|
Sign up to set email alerts
|

A new class of symmetric periodic solutions of the spatial elliptic restricted three-body problem

Abstract: We show that there exists a new class of symmetric periodic solutions of the spatial elliptic restricted three-body problem. In such a solution, the infinitesimal body is confined to the vicinity of a primary and moves on a nearly circular orbit. This orbit is almost perpendicular to the orbital plane of the primaries, where the line of symmetry of the orbit lies. The existence is shown by applying a corollary of Arenstorf's fixed point theorem to a periodicity equation system of the problem. And this existenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[5] applied the Lie transformations to the circular restricted three-body problem, and found that there exist equilibria at the cosine value ±1/ √ 5 of the inclination. The existence proof of the Hill-type nearly circular periodic orbits with large inclinations is given by Xu & Fu (2009) [6]. The authors applied double Zeipel transformations to eliminate the short periodic effects in the first-order perturbation system.…”
Section: Introductionmentioning
confidence: 99%
“…[5] applied the Lie transformations to the circular restricted three-body problem, and found that there exist equilibria at the cosine value ±1/ √ 5 of the inclination. The existence proof of the Hill-type nearly circular periodic orbits with large inclinations is given by Xu & Fu (2009) [6]. The authors applied double Zeipel transformations to eliminate the short periodic effects in the first-order perturbation system.…”
Section: Introductionmentioning
confidence: 99%
“…Chakraborty and Narayan [14] investigated the equilibrium points, linear stability, zero velocity curves, and fractal trough of the four-body constrained elliptic problem. The model cited in Xu and Fu [15] is useful as a simple example of nonintegral dynamical systems and is successful in understanding many quasiperiodic phenomena in astronomy. Ibrahim [16] studied the effect of solar radiation pressure onto the motion of many-body problem, and applied the study on the Sun-Earth-Moon-spacecraft system.…”
Section: Introductionmentioning
confidence: 99%